PREPARATION AND SURFACE-PROPERTIES OF PEO-SULFONATE GRAFTED POLYURETHANES FOR ENHANCED BLOOD COMPATIBILITY - HAN, DK; JEONG, SY; AHN, KD; KIM, YH; MIN, BG (VSP BV, 1993)
In order to improve the thromboresistance of the commercial polyurethane(PU), its surface modification was accomplished by three new different Methods and their surface characteristics were investigated using ATR-FTIR, ESCA, SEM, and dynamic contact angle measurements. Sulfonations using propane sultone were performed directly onto PU or onto hydrophobic dodecanediol (DDO) grafted PU or onto hydrophilic poly(ethyleneoxide) (PEO) grafted PU. ESCA data coincided well with ATR-IR results, as more 0 at. % for PEO grafted PUs and the presence of S for the sulfonated PUs were revealed. At SEM observation the surfaces of PU-DDO and PU-PEO were relatively smooth, whereas all the sulfonated PU surfaces showed excellent smoothness and homogeneity. The hydrophilicity of the surfaces was considerably increased after PEO grafting or sulfonation. In addition, all the sulfonated PU surfaces, particularly PU-PEO-SO3, which has further hydrophilicity, exhibited complete wetting behavior due to the negatively charged SO3 groups.
Keywords: HEPARIN-IMMOBILIZED POLYURETHANES; CHAINS